2020
DOI: 10.1111/jsr.13139
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural sleep in two species of buccal pumping sharks (Heterodontus portusjacksoni and Cephaloscyllium isabellum)

Abstract: Sleep is a conspicuous and prominent behavioural state found across the animal kingdom (Ungurean, van der Meij, Rattenborg, & Lesku, 2020). It is often associated with behavioural correlates, such as quiescence in a species-specific posture, which is rapidly reversible to wakefulness, and a decrease of awareness of the local environment resulting in an increased arousal threshold. Sleep is also regulated by two processes: (a) homeostasis, whereby sleep loss increases sleep need, causing animals to sleep more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 41 publications
3
19
0
Order By: Relevance
“…The observed diurnal peak in circling (similarly apparent in tiger sharks; Narazaki et al, 2021) also implies that sleep and coinciding reductions in energy consumption (e.g., slower tailbeats) occur primarily during the day. Diurnally reduced activity levels, responsiveness and so-called "milling" behavior suggest similar patterns in several other buccal pumping and ram ventilating species (Kelly et al, 2019(Kelly et al, , 2020Byrnes et al, 2021).…”
Section: Discussionmentioning
confidence: 78%
“…The observed diurnal peak in circling (similarly apparent in tiger sharks; Narazaki et al, 2021) also implies that sleep and coinciding reductions in energy consumption (e.g., slower tailbeats) occur primarily during the day. Diurnally reduced activity levels, responsiveness and so-called "milling" behavior suggest similar patterns in several other buccal pumping and ram ventilating species (Kelly et al, 2019(Kelly et al, , 2020Byrnes et al, 2021).…”
Section: Discussionmentioning
confidence: 78%
“…Eye states were scored as open or closed and body postures of inactive sharks were scored as flat (lying flat on the bottom of the tank) or upright (sitting perched up on pectoral fins) ( figure 1 a ). Activity states were scored as swimming, rest (inactive less than 5 min) or sleep (inactive more than 5 min); the latter has been shown to be associated with reduced responsiveness, and, therefore, a demonstrated reflection of sleep [ 17 ]. For details on statistical analyses used, see electronic supplementary material [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have found that Port Jackson ( Heterodontus portusjacksoni ) and draughtsboard ( Cephaloscyllium isabellum ) sharks are nocturnal with a reduced responsiveness to stimulation while asleep [ 16 , 17 ]. However, as sleep is both a behavioural and physiological state involving multiple components, including changes in eye state, muscle tone, brain activity and metabolism [ 18 ], it is necessary to investigate as many sleep components as possible to fully characterize the sleep state, or states, in sharks [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most fundamental and ubiquitous behaviours, sleep is shaped by ecological processes over evolutionary timescales. Sleep or sleep‐like behaviour occurs throughout the animal kingdom, in organisms ranging from jellyfish (Nath et al ., 2017) and bees (Klein et al ., 2010), to sharks (Kelly et al ., 2021) and monkeys (Nunn & Samson, 2018). It is associated with several characteristics: behavioural quiescence, typical postures, increased stimulus thresholds for arousal, rapid reversibility to wakefulness, and homeostatic regulation (Piéron, 1912; Flanigan, 1973; Tobler, 1995).…”
Section: Introductionmentioning
confidence: 99%